THE PROBLEM OF THE APPLICATION OF THE NORMS OF CONTROL IN THE MANAGEMENT PUBLISHES - Flores Konja, Julio Vicente (2010)
We consider three key aspects of the problem allows the existence of implementation of control standards in public administration. These aspects are not able to prevent also consider other aspects that influence the existence of this problem. Such is the case of a lack of analysis, interpretation and dissemination of government control standards in professional colleges and universities in some studies, if so, that for the case of the Institute of Chartered Accountants of Lima, in 2006 of 20 academic events conducted, it was only related to each accounting close of fiscal 2005 and two relating to the Audit V Mega event, being the three events total and representing 15% of the total of 20 academic events, as can be evident in Table N.º 1. Regarding the academic activities of the Functional Committees, in 2006, the Committee on Government Management held 24 activities on a grand total level of other committees of 223, representing 10.6% of academic activities carried out, according to Table N.º 2.